2008
DOI: 10.1016/j.ijpara.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Canine echinococcosis in Kyrgyzstan: Using prevalence data adjusted for measurement error to develop transmission dynamics models

Abstract: Echinococcosis is a major emerging zoonosis in central Asia. A cross-sectional study of dogs in four villages in rural Kyrgyzstan was undertaken to investigate the epidemiology and transmission of Echinococcus spp. A total of 466 dogs were examined by arecoline purgation for the presence of Echinococcus granulosus and Echinococcus multilocularis. In addition, a faecal sample from each dog was examined for taeniid eggs. Any taeniid eggs found were investigated using PCR techniques (multiplex and single target P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
97
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 34 publications
7
97
4
Order By: Relevance
“…In contrast to other E. granulosus endemic areas, where several genotypes can coexist and can be identified in the domestic dog as the definitive host (Ziadinov et al, 2008), the identification of the E. granulosus genotype G6/7 in all E. granulosus egg isolates from dogs and from all isolates of pig and cattle origin indicate that the pig strain predominates in Lithuania. This hypothesis is further supported by the fact that E. granulosus cysts had only occasionally been recorded in cattle (0.8%) and sheep (2.7%) in a previous study (Danilevičius, 1964).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In contrast to other E. granulosus endemic areas, where several genotypes can coexist and can be identified in the domestic dog as the definitive host (Ziadinov et al, 2008), the identification of the E. granulosus genotype G6/7 in all E. granulosus egg isolates from dogs and from all isolates of pig and cattle origin indicate that the pig strain predominates in Lithuania. This hypothesis is further supported by the fact that E. granulosus cysts had only occasionally been recorded in cattle (0.8%) and sheep (2.7%) in a previous study (Danilevičius, 1964).…”
Section: Discussioncontrasting
confidence: 58%
“…The egg F/Si method was recently also shown to have a higher sensitivity for the diagnosis of Echinococcus spp. in dogs (78% for E. granulosus and 50% for E. multilocularis) when compared to arecoline purgation (Ziadinov et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…A few studies investigated the contamination of dog populations with E. multilocularis on the mid-and high-altitude grasslands (2000-4500 m) of central Asia, including southeast Kyrgyzstan and central and western China (Sichuan, Qinghai and Xinjiang provinces) where pastoralism is the main activity (Budke et al, 2005;Wang et al, 2007Wang et al, , 2010Ziadinov et al, 2008;Vaniscotte et al, 2011;Van Kesteren et al, 2013). These open landscapes are known to favour population outbreaks of a variety of small mammal species shown to be E. multilocularis intermediate hosts: Ochotona curzoniae and Ochotona cansus, Microtus limnophilus, Cricetulus kamensis in the eastern Tibetan plateau of central China, Ellobius tancrei and Microtus gregalis in Kyrgyzstan .…”
Section: E Multilocularis Transmission In Dogsmentioning
confidence: 99%
“…teeth were retrieved from one sample). In the high plateau of Kyrgyzstan, Ziadinov et al (2008) showed that domestic dogs that were allowed to completely roam or roam for part of the time and that were used for hunting were more likely to be infected with E. multilocularis based on arecoline purgation combined with PCR diagnosis (11% vs. 26% for tied and non-tied dogs, respectively). A similar result was observed on the eastern Tibetan plateau of western Sichuan (Budke et al, 2005).…”
Section: E Multilocularis Transmission In Dogsmentioning
confidence: 99%
“…Classical approaches such as conducting faecal egg examination alone did not provide adequate information for parasite identification especially for the parasites producing morphologically similar eggs. However, as shown in this and in earlier studies (Bruzinskaite et al, 2009;Davidson et al, 2009;Ziadinov et al, 2008), faecal egg examination in combination with the recently developed molecular techniques would provide results with more accuracy, and being a useful tool in surveys of zoonotic parasite infections in dogs.…”
Section: Discussionmentioning
confidence: 72%